Stoichiometric CT number calibration using three-parameter fit model for ion therapy. (July 2022) - Nakao, Minoru; Hayata, Masahiro; Ozawa, Shuichi; Miura, Hideharu; Yamada, Kiyoshi; Kawahara, Daisuke; Miki, Kentaro; Nakashima, Takeo; Ochi, Yusuke; Tsuda, Shintaro; Seido, Mineaki; Morimoto, Yoshiharu; et al.
Highlight: A novel stoichiometric CT number calibration model was developed for ion therapy. The model was validated with multiple CT scanners at radiotherapy institutes. The accuracy of the estimated stopping-power ratio was improved for lung tissue. The model reduces uncertainties in range calculations more than conventional models. Abstract: Purpose: Treatment planning for ion therapy involves the conversion of computed tomography number (CTN) into a stopping-power ratio (SPR) relative to water. The purpose of this study was to create a CTN-to-SPR calibration table using a stoichiometric CTN calibration model with a three-parameter fit model for ion therapy, and to demonstrate its effectiveness by comparing it with a conventional stoichiometric CTN calibration model. Methods: We inserted eight tissue-equivalent materials into a CTN calibration phantom and used six CT scanners at five radiotherapy institutes to scan the phantom. We compared the theoretical CTN-to-SPR calibration tables created using the three-parameter fit and conventional models to the measured CTN-to-SPR calibration table in three tissue types: lung, adipose/muscle, and cartilage/spongy bone. We validated the estimated SPR differences in all cases and in a worst-case scenario, which revealed the largest estimated SPR difference in lung tissue. Results: For all cases, the means ± standard deviations of the estimated SPR difference for the three-parameter fit method model were −0.1 ± 1.0%, 0.3 ± 0.7%, and 2.4 ± 0.6% for the lung, adipose/muscle, and cartilage/spongy bone, respectively. For the worst-case scenario, the estimated SPR differences of the conventional and the three-parameter fit models were 2.9% and −1.4% for the lung tissue, respectively. Conclusions: The CTN-to-SPR calibration table of the three-parameter fit model was consistent with that of the measurement and decreased the calibration error for low-density tissues, even for the worst-case scenario.